Geração Dinâmica de Conteúdo Personalizado para Sites de Notícias - Sousa, Jonh Ney Barbosa de; Duarte, Paulo Artur de Sousa; Santos, Gisele Pereira dos; Wanderley, Ítalo Romeiro; Josino Júnior, Francisco Ari; Tavares, Priscylla da Silva; Monteiro, Davi Jucimon; Souza, Cidcley Teixeira de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2010: Proceedings of the 16th Brazilian Symposium on Multimedia and the Web, 2010)
The press newspaper is suffering a severe crisis that was established with the advent of the Internet, which brought the spread of free high quality news. Even their online versions are facing major problems to gather resources. Experts believe that the future of online newspapers is a greater interaction with the user and the use of personal advertising. This paper presents an architectural model for generating personalized content oriented for news sites. Therefore, this aims at increasing the flexibility of the structure of online newspapers in order to encourage all sides of this issue, increasing convenience to the user while generating a more robust revenue stream to the newspapers.